"Bordados do Seridó" : uma experiência etnográfica com as bordadeiras do município de Caicó-RN - Araujo, Adrianna Paula de Medeiros (2013)
The narratives that circulate Caicó tell us that the activity of embroidery would have come to town by the eighteenth century, by the Portuguese colonizers. Initially, the embroidery worked as a constitutive element in the formation of women, especially in the construction of the role of "talented ladies", was later characterized in a income generating activity moving strongly the informal sector of the local economy. In addition to source of income, the practice of embroiderers is redefining the craft tradition, transforming the embroidery on one of the symbols of identity of the city as it reaches other markets, carrying the name "Caicó embroidery". The research aims to investigate the dynamics of artisanal embroidery production, within the family circle and its consequences after its entry in the commercial sphere. It also seeks to investigate how the activity operates within a context in which the subjects (embroiderers and intermediaries) and their distinct negotiations trigger certain discourses, particularly those related to identity and authenticity on behalf of economic, political and cultural purposes